Cell Volume Measurements by Optical Transmission Microscopy. Issue 1 (1st July 2019) - Model, Michael A.
Abstract: Cell volume is an important parameter in studying cell adaptation to anisosmotic stress, activation of monovalent ion channels, and cell death. This article describes a method for measurement of the volumes of adherent cells using a standard light microscope. A coverslip with attached cells is placed in a shallow chamber in a medium containing a strongly absorbing and cell‐impermeant dye, Acid Blue 9. When such a sample is imaged in transmitted light at a wavelength of maximum dye absorption (630 nm), the resulting contrast quantitatively reflects cell thickness; once the thickness is known at every point, the volume can be computed as well. Technical details, interpretation of data, and possible artifacts are discussed. © 2019 by John Wiley & Sons, Inc.